Lifestyle factors and risk of migraine and tension-type headache. Follow-up data from the Nord-Trøndelag Health Surveys 1995–1997 and 2006–2008. (November 2018) - Hagen, Knut; Åsberg, Anders Nikolai; Stovner, Lars; Linde, Mattias; Zwart, John-Anker; Winsvold, Bendik Slagsvold; Heuch, Ingrid
Aims: The aim of this population-based historical cohort study was to investigate the influence of lifestyle factors on the risk of developing migraine or tension-type headache (TTH). Methods: Data from the Nord-Trøndelag Health Study performed in 1995–1997 and 2006–2008 was used. A total of 15, 276 participants without headache at baseline were included. A Poisson regression was used to evaluate the associations between lifestyle factors and risk ratios (RRs) of migraine and TTH 11 years later. Precision of the estimates was assessed by 95% confidence interval (CIs). Results: Increased risk of migraine (RR 1.30, 95% CI 1.11–1.52) was found in smokers (past or current) compared to those who had never smoked. Hard physical exercise 1–2 hours per week reduced the risk of migraine (OR 0.71, 95% CI 0.54–0.94) compared to inactivity, and the risk of migraine was also lower among those who consumed alcohol (RR 0.73, 95% CI 0.57–0.94) compared to abstainers. No association was found between smoking, physical activity, alcohol use and risk of TTH. Conclusions: The main finding was that current and previous smoking was associated with increased risk of migraine, but not of TTH.